The influence of mobile self-efficacy, personal innovativeness and readiness towards students' attitudes towards the use of mobile apps in learning and teaching - Mohd Ayub, Ahmad Fauzi; Zaini, Syaza Hazwani; Wong, Su Luan; Wan Jaafar, Wan Marzuki (Human Resource Management Academic Research Society, 2017)
Mobile devices are commonly used among higher education students and becoming the daily culture of almost every students. Mobile apps is one of the applications used in teaching and learning via mobile devices. However, it is important that students should have positive attitudes towards adopting these mobile devices in learning. This study explored students’ attitudes towards integrating mobile apps in the teaching and learning process and factors corelated with their attitudes. A total of 223 undergraduate students who registered in MCLass were randomly selected from a stratified cluster sample. The research examined three factors postulated to impact students’ attitudes namely, mobile self-efficacy, personal innovativeness and readiness towards Mclass. The findings showed students had positive attitudes towards Mclass teaching and learning. Further analysis indicated students’ attitudes towards MClass were positively correlated with students’ mobile self-efficacy [r = .254; p <.01], students’ personal innovativeness [r = .404; p <.01] and readiness towards MClass [r = .718; p <.01]. Further analysis using multiple regression indicated that mobile self-efficacy (β = .145), personal innovativeness (β = .117) and readiness towards MCLass (β = .655) influence students’ attitudes towards using MCLass.